Quality of Kraft pulp of Pinus pseudostrobus L. obtained from industrial chips - Gabriel-Parra, Rosalío; Rutiaga-Quiñones, José Guadalupe; Orihuela-Equihua, Rocío; Rivera-Prado, José de Jesús; Sanjuán-Dueñas, Rubén; Carrillo-Parra, Artemio (Instituto de Ecología, A.C., 2018)
The objective of this research was to increase the yield and quality of the pulp generated from the industrial chips of Pinus pseudostrobus L. It was carried out with the industrial chips of the wood of Pinus pseudostrobus L. of SCRIBE Company in Morelia, Michoacán, México. The temperatures used were 165 °C and 170 °C, cooking times of 40 minutes and 80 minutes and loading of reagents of 18% and 22%. The response variables were: yield, kappa number, rejects and residual alkali according to the TAPPI standards. The results were analyzed using an experimental factorial design. Yield varied from 33% to 52%; kappa number of 11 to 40; The rejections from 3.4% to 25.4% and the residual alkali from 3.1 g/L to 11 g/L. The yield maximization (54.8%) gave a temperature of 162 ° C, cooking time of 40 minutes and loading of reagents of 23%. Minimizing the kappa number variable (11.2) was obtained at a temperature of 166 ° C, cooking time of 26 minutes and loading of reagents of 19%. Minimization of the rejections were presented at a temperature of 162 °C, 26 minutes of cooking and a load of reagents of 19%. Finally, the residual alkali minimization (4.9 g/L) was presented at a temperature of 169.18 °C, cooking time of 60.14 minutes and loading of reagents of 20%. The operating conditions in the cooking process provide a 50% yield relative to the initial chip percentage used and a lower kappa number of 15.8 compared to pulp results from published pine species.